2006
DOI: 10.1590/s0100-736x2006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Evidência sorológica de Pneumovírus aviário em lotes de frangos de corte em municípios de Mato Grosso do Sul

Abstract: O Pneumovírus aviário (PVA) é um importante patógeno respiratório que acomete galinhas reprodutoras e frangos de corte. Apesar da importância econômica da pneumovirose não ter sido bem elucidada em frangos de corte, sabe-se que a infecção pode induzir a formação de anticorpos específicos nestas aves, e tais reações sorológicas podem servir de base ao conhecimento da epidemiologia das infecções pelo PVA. O objetivo deste estudo foi avaliar a ocorrência de anticorpos contra PVA em lotes de frangos de corte em mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies published in Brazil have reported seroconversion in unvaccinated poultry, proving that the agent is present in industrial farms (Peres et al, 2006) and in free-range poultry (Sales et al, 2010). In any case, this serological profile observed in study 2 indicates the excellent ability of vaccines to produce protection, since the appearance of clinical signs of the disease was not observed at any time during the study.…”
Section: Evaluation Of the Performance Of A New Pentavalent Vaccine I...mentioning
confidence: 58%
“…Studies published in Brazil have reported seroconversion in unvaccinated poultry, proving that the agent is present in industrial farms (Peres et al, 2006) and in free-range poultry (Sales et al, 2010). In any case, this serological profile observed in study 2 indicates the excellent ability of vaccines to produce protection, since the appearance of clinical signs of the disease was not observed at any time during the study.…”
Section: Evaluation Of the Performance Of A New Pentavalent Vaccine I...mentioning
confidence: 58%